2019
DOI: 10.1097/ncq.0000000000000333
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Patient and Family Engagement With Reduction in Harm

Abstract: The rich data suggest a significant opportunity for reducing risk and harm by more actively engaging patients and families in the effort. Increasing patient acuity and complexity of care furthers the need for partnering with patients and families more intentionally for increased safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 13 publications
1
28
0
2
Order By: Relevance
“…At the national level, a study on Portuguese hospitals prepared in 2011 by the National School of Public Health obtained similar conclusions, i.e., an incidence rate of adverse events of approximately 11%, with 53% of the situations considered preventable [9, p. 36]. However, it has been verified that, despite continuous efforts to improve safety in hospitals, the harm caused by hospital care persists [10-12].…”
Section: Introductionmentioning
confidence: 91%
“…At the national level, a study on Portuguese hospitals prepared in 2011 by the National School of Public Health obtained similar conclusions, i.e., an incidence rate of adverse events of approximately 11%, with 53% of the situations considered preventable [9, p. 36]. However, it has been verified that, despite continuous efforts to improve safety in hospitals, the harm caused by hospital care persists [10-12].…”
Section: Introductionmentioning
confidence: 91%
“…For environment, research reveals that the hospital is usually unknown to patients and may be perceived as harsh, with unknown people and procedures and different sounds, lighting, and routines, all of which aggravate their perception and hinder wellness (15) . This same study also revealed that patients and their families can be apprehensive about requesting care when the health workers are insensitive to their needs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to paying attention to the issues that involve patient s safety, they tend to the patient's needs and help create an emotionally supportive environment. According to a study, the need to establish a partnership with patients and family members and, consequently, improve patient safety, increased due to the complexity of health care (15) . Moreover, results showed that families know the history of patients, so they are able to provide information that helps the health team understand the patient's perspective, reinforce the treatment plan, notify changes in health status, and offer comfort to the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most investigators have focused on a particular dimension of harm prevention, such as patients’ attitudes toward and comfort in asking providers about handwashing (eg four of 13 studies reported in Schwappach 49 review; Davis et al 55 ), or intervention strategies, 56 and made inferences from those results to patient safety overall. Those primary studies with a more purposeful focus on understanding patients’ attitudes and thoughts about whether they have a role in safety at the direct care level were few in number, 24,57‐60 and were sometimes combined with general care activities, 59,61 or focused on parents 62 . The general findings from these investigations included viewing their role in safety “as a right, not an obligation”, 58 to seeing their role as a “shared responsibility” with providers 60 .…”
Section: Overall Themes—patient Attitudes and Behavioursmentioning
confidence: 99%